2022
DOI: 10.1080/21623945.2022.2116790
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid A promotes mitochondrial biogenesis and mitochondrial function in 3T3-L1 adipocytes through regulation of the AMPK-PGC1α signalling pathway

Abstract: Mitochondrial dysfunction is associated with insulin resistance and type 2 diabetes (T2DM). Decreased mitochondrial abundance and function were found in white adipose tissue (WAT) of T2DM patients. Therefore, promoting WAT mitochondrial biogenesis and improving adipocyte metabolism may be strategies to prevent and reverse T2DM. Salvianolic acid A (SAA) has been found to exert anti-diabetic and lipid disorder-improving effects. However whether SAA benefits mitochondrial biogenesis and function in adipose tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For example, studies have shown that tanshinone IIA [ 27 ] and apigenin [ 23 ] can protect the mitochondria by inhibiting mitochondrial oxidative stress and improving mitochondrial dysfunction in many diseases. Cryptotanshinone [ 24 ], rosmarinic acid [ 25 ] and salvianolic acid A [ 26 ] also has been reported to be useful in promoting mitochondrial biogenesis by activating AMPK pathway. Moreover, astragaloside IV could protect podocytes from injury via ameliorating mitochondrial dysfunction in diabetic rats, as demonstrated in previous studies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown that tanshinone IIA [ 27 ] and apigenin [ 23 ] can protect the mitochondria by inhibiting mitochondrial oxidative stress and improving mitochondrial dysfunction in many diseases. Cryptotanshinone [ 24 ], rosmarinic acid [ 25 ] and salvianolic acid A [ 26 ] also has been reported to be useful in promoting mitochondrial biogenesis by activating AMPK pathway. Moreover, astragaloside IV could protect podocytes from injury via ameliorating mitochondrial dysfunction in diabetic rats, as demonstrated in previous studies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that SAA can exert antidiabetic effects, preventing diabetic complications by reducing inflammatory response and improving lipid disorders (13), revealing the possible therapeutic effect of SAA on DM (14). Diabetes with MI/RI are not sensitive to pre-, post-conditioning cardioprotective interventions that are otherwise effective in nondiabetic subjects, while the related mechanisms are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The PGC-1α/Nrf/TFAM/mtDNA signalling pathway has been confirmed in many disease models, such as peritoneal fibrosis associated with peritoneal dialysis, type 2 diabetes mellitus, and ulcerative colitis. [11][12][13].…”
Section: Introductionmentioning
confidence: 99%